HUBUNGAN PERAN DAN FUNGSI KELUARGA DENGAN TINGKAT KECEMASAN PADA PASIEN DENGAN PENYAKIT TIDAK MENULAR - Maila Faiqoh Tsauroh (2022)
The prevalence of Non-Communicable Diseases (NCD) increases every year. This is due to population changes, modernization and globalization that affect a person's lifestyle, such as unhealthy eating patterns and smoking behavior which are risk factors for NCD. This has an impact on the psychological condition of NCD sufferers who will experience anxiety due to their illness and the treatment process. To be able to reduce this anxiety, it is necessary to have a good family role and family function. The purpose of this research is to determine the relationship between function and the level of anxiety of patients with NCD at the Rumah Sehat Terpadu Dompet Dhuafa Hospital, Bogor, by using a cross-sectional approach. The total of samples that met the inclusion criteria was 180 people using purposive sampling technique. The results of bivariate analysis using the Spearman test in this research obtained P-value (0.000) < P-value (0.05). In this research, there was a significant relationship between family roles and family functions with anxiety levels in NCD patients. Families will be desirable to build effective family roles and functions so that patients with PTM can overcome their anxiety.